Trends in changes of family functioning during different phases of the pandemic - findings across four population-based surveys between 2020 to 2023 in Germany - Alina Geprägs; David Bürgin; Jörg M. Fegert; Elmar Brähler; Vera Clemens (BMC, 2024)
Abstract Background The COVID-19 pandemic and the associated measures have had a significant impact on millions of individuals and families worldwide. Although cross-sectional studies have demonstrated the considerable burden placed on families during the pandemic, trends over different phases of the pandemic including later stages and using population-based samples is scarce. Objective In this study, we aimed to assess trends in family functioning across four population-based surveys between December 2020 and March 2023 using a repeated cross-sectional design. The surveys were conducted using a similar sampling strategy and measures. We included individuals residing in a household with at least one minor below the age of 16. Results The most notable changes across surveys over time were related to quality of life. While 54.3% of respondents reported a decline in quality of life during the winter of 20/21 compared to pre-pandemic levels, this was observed in only 22.6% of participants during the spring of 23. The proportion of respondents who indicated a deterioration in their relations with their children also decreased during the pandemic. While 9.9% of respondents reported a deterioration in their relationship with their children during the winter of 20/21 in comparison to the initial phase of the pandemic, this was reported by only 5.2% in the spring 23. The relationship with one's partner and health status exhibited minimal fluctuations. Mental health problems were associated with a decline in quality of life, health status and relationships with children and partners compared to pre-pandemic levels at all time points. Moreover, lower income levels were associated with poorer relationship quality with the partner in the most recent wave. Conclusions Our findings demonstrate significant improvements in family functioning since the onset of the pandemic, indicating that individuals and families in our sample were generally adapting well. However, a subgroup of the population still reports suboptimal family functioning compared to before the pandemic. Psychosocial care and social policy support for families are needed.